Adobe Photoshop CS4 illustrated - Botello, Chris. 4 0 16; 5 (Australia ;;Boston : Course Technology, 2010)
A guide to using the Adobe Photoshop CS4 program that offers step-by-step instructions for completing various tasks, real-world examples, a CD containing all the data files needed for the lessons, and screenshots to help students complete each exercise.
Includes index.
Adult;Adult
System requirements for PC and Mac stated on p. xvi.
Keywords: 2 -- 0; 6; Adobe Photoshop.;Adobe Photoshop; Digital techniques.;Computer programs. -- Image processing;Computer graphics;Computer graphics; 20; 2